2014
DOI: 10.1016/j.physletb.2014.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Strange quark matter fragmentation in astrophysical events

Abstract: The conjecture of Bodmer-Witten-Terazawa suggesting a form of quark matter (Strange Quark Matter) as the ground state of hadronic interactions has been studied in laboratory and astrophysical contexts by a large number of authors. If strange stars exist, some violent events involving these compact objects, such as mergers and even their formation process, might eject some strange matter into the interstellar medium that could be detected as a trace signal in the cosmic ray flux. To evaluate this possibility, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 41 publications
(57 reference statements)
1
42
1
Order By: Relevance
“…It is observed that ignoring critical aspects of the quantum particle physics in the framework of GR several authors [91][92][93][94][95][96][97][98] successfully have been introduced this simplified form of the MIT Bag EOS to study stellar systems made of SQM.…”
Section: Basic Stellar Equations In F (R T ) Theory Of Gravitymentioning
confidence: 99%
“…It is observed that ignoring critical aspects of the quantum particle physics in the framework of GR several authors [91][92][93][94][95][96][97][98] successfully have been introduced this simplified form of the MIT Bag EOS to study stellar systems made of SQM.…”
Section: Basic Stellar Equations In F (R T ) Theory Of Gravitymentioning
confidence: 99%
“…It is observed that to describe a stellar model made of strange quark matter well known MIT bag EOS can be considered under such a situation. Successful use of the MIT bag EOS to describe strange quark stars the following recent works are available in the literature [31,32,33,34,35,36,37,38]. This type of simplest form of EOS is very useful to study equilibrium configuration of a compact stellar object made of only up, down and strange quarks even in the framework of general relativity without invoking any quantum mechanical particle physics aspect.…”
Section: Introductionmentioning
confidence: 99%
“…At a microscopic level, a dynamical study of the droplet boundary once formed has not been studied in detail yet. If the full NS converts to a more compact QM star this exotic type of matter would be ejected leaving an imprint on the cosmic rays or scintillation patterns [55][56][57]. Boundary conditions for isolated clusters have been somewhat explored in [58] where, arising from the strange quark content, the name of strangelet is coined.…”
Section: Resultsmentioning
confidence: 99%